Efficacy and Safety of Dual Antiplatelet Therapy Using Cilostazol with Aspirin or Clopidogrel to Reduce the Rate of Recurrent Ischemic Stroke in Asia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Hendrawan Chandra Kusuma; Guntur Yohanes; Eugenia Isadora; Husnul Khotimah; Patricya Vira Heumasse; Ayers Gilberth Ivano Kalaij (Siriraj Medical Journal)
Objective: The stroke mortality rate in Asia is higher than in other regions worldwide. As an antiplatelet medication and phosphodiesterase-3 inhibitor, cilostazol lacks approval for use in ischemic stroke. We intended to analyze the efficacy and safety of cilostazol dual antiplatelet therapy (DAPT) with clopidogrel or aspirin compared to aspirin or clopidogrel monotherapy.